PENGARUH PEMAHAMAN STANDAR AKUNTANSI PEMERINTAHAN, PENDIDIKAN DAN PELATIHAN TERHADAP PENYUSUNAN LAPORAN KEUANGAN SKPD KOTA BINJAI - , Galih Supraja (Jurnal Akuntansi Bisnis dan Publik, 2020)
The purpose of this study is to determine whether Understanding of Government Accounting Standards, Education and Training simultaneously influences the Preparation of Binjai City Government Financial Statements. The population in this study are employees of the financial department in charge of preparing financial reports on 29 SKPD. The data used are primary data obtained by distributing 87 sets of questionnaires to financial report compiler tools in 29 SKPD of Binjai City Government. From the distribution of questionnaires the data returned and can be processed amounted to 42 sets of questionnaires. Data analysis methods used in this study were data quality tests consisting of validity and reliability tests, classic assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests and multiple linear analysis tests and hypothesis tests consisting of t tests, F and determination test. The results of this study simultaneously by carrying out the F test obtained Understanding of Government Accounting Standards, Education and Training affect the Preparation of Binjai City Government Financial Statements. The conclusion in this study is the Understanding of Government Accounting Standards, Education and Training simultaneously influences the preparation of Binjai City government financial statements of 37.6% and the remaining 62.4% is influenced by other factors not discussed in this study.